GE_GERICHTE P/3416/2016 vom 2. März 2020 - GE Cour de justice (2020)
ESCROQUERIE;VOL D'USAGE;SÉJOUR ILLÉGAL;VIOLATION DE DOMICILE;VIOLATION DES RÈGLES DE LA CIRCULATION;DOMMAGES À LA PROPRIÉTÉ(DROIT PÉNAL) | CP.139.al1; CP.144.ch3; CP.196; CP.146.al1; LCR.90.al2; LEI.I.leta; CP.139.al1.ch22